Effect of oral contraceptives on the anticoagulant activity of protein S in plasma - Koenen, Rory R.; Thomassen, Christella M. L.G.D.; Tans, Guido; Rosing, Jan; Hackeng, Tilman M. (Thrombosis and Haemostasis, 2005)
We determined anticoagulant parameters that depend on protein S function in plasma, i.e.the APC-independent anticoagulant activity of protein S (expressed as pSR) and APC resistance determined with thrombin generation-based tests (expressed as APCsr) as well as plasma levels of total and free protein S and prothrombin in men, women not using oral contraceptives (OC), and in women using second or third generation OC. Thrombin generation in the APC resistance assays was initiated either with factor Xa (Xa-APCsr) or tissue factor (TF-APCsr). The APC-independent anticoagulant activity of protein S was highest in men (pSR=1.69) and gradually decreased from women not using OC (pSR=1.49) via women using second generation (pSR=1.35) to women using third generation OC (pSR=1.27). The pSR correlated inversely with nAPCsr determined with the tissue factor-based APC resistance test (TF-APCsr) but not with nAPCsr determined with the factor Xa-based assay (Xa-APCsr). Multiple linear regression analysis in which sex, OC use, and protein S and prothrombin levels were included as independent variables and the pSR, TF-APCsr or Xa-APCsr as dependent variables indicated that plasma protein S levels poorly predict the pSR and the TF-APCsr, but are the main determinant of the Xa-APCsr. This indicates that OC use alters the expression of protein S activity. This phenomenon can be caused by differences in modulation of the activity of protein S by other plasma proteins that change during OC use or by OC-induced changes in the protein S molecule that impair its anticoagulant activity. Functional impairment of protein S as a result of hormonal influence may, at least in part, contribute to the thrombotic risk of OC users.
Keywords: Protein S; oral contraceptives; APC-resistance; pSR; thrombosis